Vorasidenib for IDH-mutant grade 2 gliomas: clinical advances and future directions - Pan, Zhenjiang; Bao, Jing; Wei, Shepeng (Frontiers in Oncology, 2025)
Vorasidenib, a brain-penetrant dual inhibitor of mutant isocitrate dehydrogenase 1 and 2 (IDH1/2), represents a significant advancement in the management of IDH-mutant gliomas. This review explores the clinical implications of its recent FDA approval for grade 2 IDH-mutant astrocytomas and oligodendrogliomas. We delve into the pivotal INDIGO trial, which demonstrated substantial improvements in progression-free survival, and discuss vorasidenib’s pharmacokinetics, safety profile, and dosing guidelines. Additionally, we analyze its role within evolving treatment paradigms, including watchful waiting, IDH-targeted therapy, and integration with radiotherapy and chemotherapy. Comparative insights into traditional and novel approaches highlight the potential of vorasidenib to delay invasive therapies while preserving quality of life. Challenges such as adverse effects, long-term safety, and its application to higher-grade gliomas are also addressed. This comprehensive review underscores the transformative impact of vorasidenib and emphasizes the necessity of multidisciplinary care and patient-centered decision-making in glioma management.